Internet Financial Reporting by Saudi Companies - Ali Khan, M. N. A.; Bajaher, M. S. A.; Ismail, N. A. (Universiti Sains Islam Malaysia, 2024)
This study explores the status of Internet Financial Reporting (IFR) behavior of 84 companies listed in Saudi Stock Market. The results reveal that 66 (79%) of these companies maintain websites. Of these 66 companies, only 39 (59%) provided some forms of financial information on their websites. The findings indicate that the status of IFR among Saudi's listed companies is still behind those of developed countries and even some developing countries like Malaysia. This study then examines factors that infuence the extent of IFR. Three factors associated with voluntary disclosure are examined: company size, leverage and profitability. Results of multiple regression analysis indicate that company size and profitability contributed significantly to the extent of IFR among Saudi companies. Policy implications and possible limitations of the study as well as suggestions for future research are discussed in the study. More importantly, it opens up possibilities for further study of IFR among Gulf countries.